Combined synthetic and recombinant techniques for the development of lipoprotein-based, self-adjuvanting vaccines targeting human papillomavirus type-16 associated tumors. Issue 23 (1st December 2015) - Moyle, Peter M.; Dai, Wei; Liu, Tzu-Yu; Hussein, Waleed M.; Maruthayanar, Pirashanthini; Wells, James W.; McMillan, Nigel A.J.; Skwarczynski, Mariusz; Toth, Istvan
Graphical abstract: Abstract: Human papillomaviruses (HPVs) are associated with various cancers, with HPV16 linked to more than half of cervical cancer cases. Vaccines to prevent HPV infection and cancer development have proven effective, but are not useful in individuals with prior HPV exposure. Treatment vaccines to eradicate or control HPV-associated lesions are therefore desirable for these patients. Herein we describe the development of a process to enable the production of semisynthetic vaccines based on the site-specific attachment of synthetic bacterial lipid analogs (e.g., Pam2Cys) to a non-oncogenic mutant HPV16 E7 protein to generate molecularly defined vaccines. Many cytotoxic lymphocyte (CTL) epitopes from E7 are delivered by this approach; potentially ensuring that large numbers of immunized individuals can generate CTLs to clear HPV infected cells. Delivery of this construct reduced the growth of HPV16-associated tumors in a TC1 mouse model, the effects of which were better than the potent CTL epitope HPV16 E7(44–57) administered with Montanide ISA51 adjuvant.